Brucella canis discospondylitis in 33 dogs - Long, Christina; Burgers, Elisabeth; Copple, Christina; Stainback, Laura; Packer, Rebecca A.; Kopf, Kelli; Schmidt, Jessica; Emch, Samantha; Windsor, Rebecca (Frontiers in Veterinary Science, 2022)
Objective: To describe the clinical and imaging findings of 33 dogs with Brucella canis discospondylitis (BDS) Animals: 33 client owned dogs from four veterinary specialty hospitals within Colorado and Arizona with at least one positive B. canis test and spinal diagnostic imaging Procedures: Retrospective review of signalment, physical and neurological examination findings, laboratory results, B. canis serology, and diagnostic imaging of 33 dogs with BDS. All imaging was reviewed by a board-certified veterinary neurologist. Radiographs were reviewed by a board-certified veterinary radiologist blinded to MRI and CT findings. Results: 31/33 (94%) dogs were <5 years old (median=2.5 years, mean=2.9 years, range 0.5-10 years). 21/29 (72%) dogs had signs of nonspecific pain, spinal pain, or lameness for >3 months (median=6 months, mean=8.2 months, range 5 days-4 years). Fever was seen in only 4/28 (14%) dogs. Multifocal lesions were evident on radiographs in 21/29 (72%) dogs and MRI in 12/18 (67%) dogs. Smooth, round, central end-plate lysis, defined as “hole punch” lesions, were identified radiographically in 25/29 (86%) dogs. Vertebral physitis or spondylitis without discitis was evident on MRI in 7/18 (39%) dogs. Clinical Relevance: Dogs with BDS typically present at a young age with a long duration of clinical signs. Identification of radiographic “hole punch” lesions and MRI evidence of vertebral physitis, spondylitis, and paravertebral inflammation without discitis should increase suspicion for BDS. BDS may be increasing in frequency in the southwestern United States, and dogs with signs of chronic spinal pain and/or lameness should be screened for B. canis.